Critical success factors affecting technology transfer effectiveness: A study on electric and electronic companies in manufacturing industry in Malaysia - Mohamad Sukri, Nor Hafizah; Ibrahim, Amlus; T., Ramayah (2010)
Critical success factors are critical factors or activities required for ensuring the success of your business.The term was initially used in the world of data analysis, and business analysis.Critical success factors have been used significantly to present or identify a few key factors that organizations should focus on to be successful. The key to using CSFs effectively is to ensure that organizations definition of a factor of their organizations activity which is central to its future will always apply.Therefore success in determining the CSFs for organizations is to determine what is central to its future and achievement of that future.Some researcher also indicated that identifying CSF’s is important as it allows firms to focus their efforts on building their capabilities to meet the CSF’s, or even allow firms to decide if they have the capability to build the requirements necessary to meet Critical Success Factors (CSF’s).Furthermore, in any organization certain factors will be critical to the success of that organization, in the sense that, if objectives associated with the factors are not achieved, the organization will fail and perhaps trouble so.There are four basic types of CSF’s, there are: Industry CSF’s resulting from specific industry characteristics; Strategy CSF’s resulting from the chosen competitive strategy of the business; Environmental CSF’s resulting from economic or technological changes; and Temporal CSF’s resulting from internal organizational needs and changes. Each CSF should be measured and associated with a target goal.Not exact measures to manage are needed. Primary measures that should be listed include critical success levels (such as number of transactions per month) or, in cases where specific measurements are more difficult, general goals should be specified (such as moving up in an industry customer service survey).Not only that, CSF’s are tailored to a firm’s or manager’s particular situation as different situations (e.g. industry, division, individual) lead to different critical success factors.There are five key sources of CSF’s which are: the industry, competitive strategy and industry position, environmental factors, temporal factors, and managerial position (if considered from an individual’s point of view).We will carry out hypothesis testing using SPSS. Sample for this study will be selected from directory of Federal Manufacturing of Malaysia (FMM).This study will give significant impact toward manufacturer in implementing technology transfer process.